(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Milling process is used to remove material by a rotating cutter. This machining procedure is commonly employed by industries, and it involves cutting away any unneeded material. On a part, a milling machine is used to create a variety of characters. a The goal of this research is to determine the optimum surface roughness, which is a machine parameter. One of the most particular customer needs in a machining process is surface roughness. Surface roughness refers to minor texture abnormalities on the surface. In the machining process, surface roughness is also caused by the tool chip contact and feed marks. In measuring the productivity of machine tools and machined products, the quality of the surface plays an essential role. Several milling process factors, including as cutting speed, feed, cutting depth, rate of material removal, also known as MRR, and machine time, all play a crucial impact in surface roughness. Many investigations have focused on these factors, and it has been discovered that the process parameters cutting speed, depth of cut, and feed are essential characteristics that determine the work piece’s surface roughness. So, in terms of optimization, these three process parameters (feed, cutting depth, and cutting speed) should be chosen. To discover the best value of parameters for cutting and minimizing surface roughness, an appropriate optimization approach is required. To achieve the best surface roughness, the Taguchi method will be utilized. To identify the parameter setting, Taguchi’s orthogonal array should be employed. The results will be analyzed using analysis of variance (ANOVA). Mild steel will be utilized in milling machines with water cooling to carry out the machining operation.